Researching and developing the emotional intelligence of History teachers in the Lejweleputswa District, Free State (South Africa) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
This article reports on case-study research into the emotional intelligence of secondary school History teachers of the Lejweleputswa District of the Free State Province of South Africa. It reflects on how the emotional intelligence of these teachers can be understood through investigating their experiences and attitudes towards History teaching in the modern South African classroom and reveals why they regard History as particularly challenging to teach. The article also explores how emotional intelligence components such as interaction style, flexibility, assertiveness and listening skills influence both the classroom interaction of these teachers with their learners and their professional relations with colleagues. Moreover, it argues that improved emotional maturity can empower these teachers to manage their emotions effectively, cope with the demands of a stressful profession, handle conflict in the classroom, and teach History with greater creativity, effectiveness and confidence. It further shares the views of the participants in this first-phase emotional intelligence intervention on the value of the training for their professional and personal development, and conveys the passion with which these educators teach their subject in challenging circumstances. Finally, the article highlights the need for a more comprehensive programme which should ideally be extended to History teachers in the rural areas and educators teaching subjects other than History.
Keywords: Secondary school History teachers; Emotional intelligence; History teaching; Professional development; Lejweleputswa district; Free State province; Interaction style; Flexibility; Assertiveness; Listening skills